2022
DOI: 10.1155/2022/7295224
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cr(VI)-Induced Premature Senescence in L02 Hepatocytes by ROS-Ca2+-NF-κB Signaling

Abstract: Stress-induced premature senescence may be involved in the pathogeneses of acute liver injury. Hexavalent chromium [Cr(VI)], a common environmental pollutant related to liver injury, likely leads to premature senescence in L02 hepatocytes. However, the underlying mechanisms regarding hepatocyte premature senility in Cr(VI) exposure remain poorly understood. In this study, we found that chronic exposure of L02 hepatocytes to Cr(VI) led to premature senescence characterized by increased β-galactosidase activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…For example, IL-6 and IGFBP2 are much lower in the non-senescent cells isolated from the fat tissue of young mice than the senescent cells from the same tissue. Similarly, our previous research also identified the increased level of IL-6 in the premature senescent cells induced by hexavalent chromium (Zhang et al, 2022). Interestingly, the primordial function of SASP is to recruit the immune cells to remove senescent cells, but it could propagate from cell to cell potentially aggravating the senescent cell burden of chronic disease progression when the ability of immune cells to clear senescent cells is overcome; thus, it can be seen that the secretion of may further influence microenvironments and cause senescent phenotypes in the surrounding normal cells.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…For example, IL-6 and IGFBP2 are much lower in the non-senescent cells isolated from the fat tissue of young mice than the senescent cells from the same tissue. Similarly, our previous research also identified the increased level of IL-6 in the premature senescent cells induced by hexavalent chromium (Zhang et al, 2022). Interestingly, the primordial function of SASP is to recruit the immune cells to remove senescent cells, but it could propagate from cell to cell potentially aggravating the senescent cell burden of chronic disease progression when the ability of immune cells to clear senescent cells is overcome; thus, it can be seen that the secretion of may further influence microenvironments and cause senescent phenotypes in the surrounding normal cells.…”
Section: Introductionsupporting
confidence: 69%
“…It has been reported that senescent cells often secrete various proteins with potent effects, including cytokines, chemokines, growth factors, or MMPs (Wiley and Campisi, 2021). As our previous research found that the levels of IL-6 and FGF23 were profoundly increased in the hexavalent chromiuminduced premature senescent hepatocytes (Zhang et al, 2022). Similarly, parkinsonian SNpc tissues displayed elevated protease MMP-3 and pro-inflammatory cytokines IL-6, IL-1α, and IL-8 (Chinta et al, 2018).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous studies have shown that intracellular calcium overload can increase the expression of NF-κB. 67 , 68 NF-κB is a nuclear transcription factor, and its excessive activation is closely related to cell proliferation and increased expression of inflammatory factors. 69 , 70 The results showed that fatty oil, OIL-NPs and PLC inhibitor could reduce the expression of NF-κB and the mRNA expression levels of TNF-α, IL-6 and IL-1β, and the effect of OIL-NPs was better than that of fatty oil.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated that Cr(VI) exposure could induce acute hepatotoxicity related to liver failure/injury in mice and cell apoptosis [ 56 ]. In addition, chronic hepatotoxicity was also the result of low-dose and long-term Cr(VI) exposure, manifested as the premature senescence of hepatocytes [ 57 ]. Wang et al reported the effects of single oral exposure to Cr(VI) in mice liver, showing that Cr(VI) could induce hepatocyte apoptosis in vivo [ 58 ].…”
Section: Er Stress and Xenobiotic-induced Hepatotoxicitymentioning
confidence: 99%